AN ANALYSIS OF INFLECTIONAL AFFIXES IN THE DISCOURSE ON THE METHOD TEXT BY RENE DESCARTES - Seprudin (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2022)
The Objective of the study is to know about the process of inflectional affixes changing in the “Discourse on the Method Text by Rene Descartes”. This study applied qualitative method. This analysis used theory of George Yule, O’Grady and Guzman, and Mc-Carty. This study discussed about inflectional affixes changing based on Comparative, Superlative and Past tense form. The result of this studies is inflectional affixes changing occur in comparative, superlative and past tense form in the Discourse on the Method Text by Rene Descartes.